Comparison between biological and chemical control to overcome Metisa Plana infestation / Siti Nur Fitrah Abd Malik - Abd Malik, Siti Nur Fitrah (Faculty of Plantation and Agrotechnology, 2018)
Oil palm is the main crop commodity in Malaysia and now Malaysia being the second largest producer of oil palm after Indonesia by 17200 export volume per metric tonnes. Malaysian has two equal regions roughly which is Peninsular Malaysia and Malaysian Borneo (Otieno et.al, 2016). Bagworm now become the major pest of oil palm instead of rhinoceros beetle. Bagworm is one of the most leaf eating pest of oil palm that mostly attack in Malaysia and Indonesia (Norman, 2016). The main objective of this study is to assess yield production through chemical and biological control and to compare the bagworm collected for biological control at three different trap location. This study will be carried out at RISDA Changkat sulaiman, Perak. The location was choosen based on the severe outbreak of the bagworm. This area is having flat topography and not too sloopy with proper road network reaching to the area. The total area of the oil palm in RISDA Changkat Sulaiman is 917.27 hectare. The method for biological control are using mass trapping of bagworm. Two plot or stage of oil palm trees which is 16 years old and 6 years old are selected for this experiment because both stage are having an outbreak of bagworm at this RISDA. 1 ha of oil palm tree consist of 148 trees. Then for the chemical control are using trunk injection carried out on 15 years old oil palm trees in RISDA Semaian. From the graph produced, the highest yield produced is 116.2m/tan, which is by using the chemical control. The production of yields from the first month to the fourth months shows an increasing trend for both chemical and biological control. For the data collection for biological control in three different location, the significance value is 0.000 meaning that we reject the null hypothesis. There is significant difference between on the bagworm collected at three different trap location. Biological control is one of the good ways to control the Metisa plana but still chemical control by using trunk injection is more effective because it give faster effect in long term period.